2020
DOI: 10.1007/s10096-020-03841-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of respiratory syncytial virus IgG antibody dynamics in mother-infant pairs cohort

Abstract: RSV is one of the most important agents of lower respiratory infections in childhood. In this study, anti-RSV antibody levels in mother-infant pairs and factors related to antibody transfer ratio were investigated. One hundred and twenty-seven women that had term babies and their babies and 84 mother-infant pairs of them who continued the study after 6 months were enrolled. Anti-RSV IgG antibodies of the mothers and infants were positive in 46.5% and 61.5%, respectively. At the sixth month, anti-RSV antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
1
6
1
Order By: Relevance
“…The presence of RSV IgG antibodies in infants could interfere with viral‐induced immunogenicity, 22 but on the other hand, the transplacental transfer of protective maternal antibodies could be helpful in preventing severe disease in infants 23 . Maternal anti‐RSV IgG are significantly higher in infants with siblings, supporting the hypothesis that RSV exposure during pregnancy correlates with the levels of protection 24 …”
mentioning
confidence: 93%
See 1 more Smart Citation
“…The presence of RSV IgG antibodies in infants could interfere with viral‐induced immunogenicity, 22 but on the other hand, the transplacental transfer of protective maternal antibodies could be helpful in preventing severe disease in infants 23 . Maternal anti‐RSV IgG are significantly higher in infants with siblings, supporting the hypothesis that RSV exposure during pregnancy correlates with the levels of protection 24 …”
mentioning
confidence: 93%
“… 23 Maternal anti‐RSV IgG are significantly higher in infants with siblings, supporting the hypothesis that RSV exposure during pregnancy correlates with the levels of protection. 24 …”
mentioning
confidence: 99%
“…The half-life of RSV-specific antibodies in infants was approximately 40 days and there was no evidence of severe RSV disease in infants of vaccinated mothers [119]. Considering that the antibody transfer rate was the highest in appropriate-for-gestational-age infants, maternal vaccination strategies may be less effective in small-for-gestational-age and large-for-gestational-age infants [120]. A modeling study for the period 2023-2035 revealed that a maternal RSV vaccine with 60% efficacy offering 5 months of infant protection implemented across 73 low-and middle-income Global Alliance for Vaccines and Immunizations (Gavi)-supported countries could avert 10.1-12.5 million cases, 2.8-4.0 million hospitalizations, 123.7-177.7 thousand deaths, and 8.5-11.9 million disability-adjusted life-years among infants aged <6 months, suggesting that RSV maternal immunization could substantially reduce mortality and morbidity among infants [121].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, premature infants may not benefit from a maternal immunization strategy. In a study performed by Yildiz et al, antibody transplacental transfer rates were lower in small for gestational age and large for gestational age infants in comparison to those appropriate for gestational age, but these observations have not been replicated (47,48).…”
Section: Disease Preventionmentioning
confidence: 95%